KEMAMPUAN MEMBACA PEMAHAMAN TEKS DESKRIPSI DAN KEMAMPUAN MENULIS TEKS ESKPOSISI SISWA KELAS VIII SMP NEGERI 13 PEKANBARU - Siska Deswita; Charlina Charlina; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses the ability to read comprehension of text description and the ability to write the text of the students' exposition of the viii smp class in the 13th week. The sample used in this research is 100. The method in this research is inferential statistic. The results of this study indicate the acceptance of Ho in Chi Square Test meaning that the data is normal and can be continued on the parametric inferential statistical test. Furthermore, t test that produces rejected Ho means that the ability to read the understanding of text description and the ability to write exposition text students of class VIII SMP Negeri 13 Pekanbaru classified as very lace, medium, or high. very low, medium or high reading ability understanding of text description and ability to write the exposition of siwa text is known by comparing the authors hypothesis with test results t. Furthermore, a direct ANOVA test is performed which results in Ho's rejection meaning that there is a mean difference between classes or there are differences in the ability of each class. Furthermore, to find out whether there is a relationship between reading class understanding of text description and writing exposition text it will be done product-moment correlation testing. The test resulted in a correlation between the reading ability of the text of the description text and the exposition text writing insignificant.Keywords: Reading, Writing, Text Exposition